Bio-activity of Algae Belonging to Bhusawal region, Maharashtra - Mahajan2 and R.T.Mahajan3, K. J. Patil1, Vidya A Patil2, S.R. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Three algal species; Spirogyra (A), Chara (B) and Cladophora (C) were isolated from Tapi river near Bhusawal (M.S.). These algae were tested in compliance with the agar well diffusion method for their antibacterial and antifungal agent production on various organisms that incite diseases to human and plants (Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Proteus vulgaris, Asperigillus niger and Candida albicans). The bioactive metabolites are extracted by using diethyl ether, butanol, acetone and methanol. It was found that; sample A had the highest bioactivity towards the tested bacteria. Algae are found to be rich source nutrients like carbohydrates, lipids and proteins. Thus they act as growth promoting substance for fungi like Candia albicans and Asperigillus niger. From tested algae B has highest growth promoting ability for fungi Candia albicans and Asperigillus niger.